BSA and humic acid separation from aqueous stream using polydopamine coated PVDF ultrafiltration membranes. Issue 3 (June 2017) - Sri Abirami Saraswathi, M.; Kausalya, R.; Kaleekkal, Noel Jacob; Rana, D.; Nagendran, A.
Graphical abstract: Highlights: Polydopamine (PD) coated antifouling poly (vinylidene fluoride) (PVDF) ultrafiltration (UF) membranes were successfully fabricated. PD coated PVDF membranes demonstrated higher hydrophilicity, water permeation and flux recovery ratio (FRR) than pristine PVDF membrane. PVDF/PEG/PD membrane displayed the best antifouling tendency when the feed was an aqueous bovine serum albumin (BSA) and humic acid (HA) solutions. Abstract: To inhibit the inherent hydrophobicity and low anti-fouling of poly (vinylidene fluoride) (PVDF) ultrafiltration (UF) membranes, poly (ethylene glycol) (PEG) and polydopamine (PD) were successfully utilized. Neat and PD coated PVDF membranes were prepared with and without the addition of PEG. PD coating on PVDF membrane surface was confirmed by attenuated total reflectance - Fourier transform infrared (ATR-FTIR) spectroscopy. To analyze the bulk as well as surface hydrophilicity, water content and contact angle measurements were made. The PVDF/PEG/PD membrane exhibited the highest pure water flux (118 Lm −2  h −1 ), water content (73.2%) and a lower water contact angle (61.5°), all of which confirms the improvement in hydrophilicity. The SEM imaging evidently demonstrated the notable morphological changes of the PVDF membrane after the modifications with PEG and PD. This PEG and PD modified membrane shows the lowest hydraulic resistance owing to the effect of the pore forming agent and a hydrophilic layer of PD. Humic acid (HA) and bovine serum albumin (BSA) were employed as foulants to analyze the separation performance and fouling resistance of the membranes. The PVDF/PEG/PD membrane exhibited the highest fluxes of 96.4 and 81.4 Lm −2  h −1 with rejections of 90.5% and 95.4%, respectively, when tested for BSA and HA solutions. It also showed a higher flux recovery ratio of 92.0% and 81.4% after the filtration of BSA and HA solutions, respectively. These results demonstrated that the superior permeation, separation and antifouling behavior of PVDF/PEG/PD membrane and thus promising for possible use as UF membrane in water and waste water treatment.